102k views
22 votes
AAHHHHHHHHHHHHHHHHHH

AAHHHHHHHHHHHHHHHHHH-example-1
User Jake Reece
by
5.0k points

1 Answer

3 votes

Explanation:


(1 - \cos \theta)/(1 + \cos \theta) = (\sec \theta - 1)/(\sec \theta + 1)


(1 - \cos \theta)/(1 + \cos \theta) = ((1)/(\cos \theta) - 1)/((1)/(\cos \theta) + 1)


(1 - \cos \theta)/(1 + \cos \theta) = (\cos \theta)/(\cos \theta) * ((1)/(\cos \theta) - 1)/((1)/(\cos \theta) + 1)


(1 - \cos \theta)/(1 + \cos \theta) = ((\cos \theta)/(\cos \theta) - \cos \theta)/((\cos \theta)/(\cos \theta) + \cos\theta)


(1 - \cos \theta)/(1 + \cos \theta) = (1 - \cos \theta)/(1 + \cos\theta)

User Orville Jackson
by
5.2k points